Acute bacteremic pneumonia due to melioidosis developing in the intensive care setting - Zainal Abidinan, Huda; Muhd Besari, Alwi; Nadarajan, Chandran; Wan Shukeri, Wan Fadzlina; Mazlan, Mohd Zulfakar; Soon, Eu Chong; Ayub, Zeti Norfidiyati Salmuna (Elsevier, 2017)
In Malaysia, melioidosis is commonly encountered as this infection is known as part of the endemic area for the disease. Managing cases of positive Burkholderia pseudomallei infection can involve multidisciplinary unit mainly, microbiologist, infectious disease team and intensive care as it may be quite difficult to distinguish melioidosis from a number of other diseases on the clinical setting alone. Laboratory diagnosis plays a vital role in determining the direction of management. Investigations such as culture, polymerase chain reaction (PCR) and serology should be evaluated once the disease is suspected. In this particular case, the patient is a young adult involved in a road traffic accident. Unlike any other cases with melioidosis, he had no potential risk factors which may have contributed to the severity of the disease and it is likely that the site of the accident was the source of acquisition of this gram negative bacterium.